(untitled) (Research, Society and Development, 2021)
Oral mucocele is considered the most common benign lesion of the minor salivary glands, corresponding to a phenomenon of retention or extravasation of mucus. Oral mucoceles originate through mechanical trauma, and most often affect the lower lip, as it is a region more prone to trauma. This article aims to present a clinical case of a 21-year-old patient complaining of volumetric increase in the lower lip, with one year of evolution and who did not present episodes of rupture or remission. Under the diagnostic hypothesis of mucocele, the lesion was excised in the lower lip, where the mucosal incision was precisely delimited with the aid of a biopsy punch and the lesion, with the minor salivary glands, were removed by dissection with iris scissors. The definitive diagnosis obtained after histopathological analysis was mucocele, confirming the hypothesis initially presented. The clinical case presented obtained a satisfactory result with the technique used, allowing good evolution, with no infection and no recurrence.